Implementasi Aplikasi Manajemen Stok Dengan Metode FIFO Untuk Optimalisasi Inventori: Studi Kasus Aziz Helmet Store - Darip, Mochammad Darip; Rohman, Ali; Aziz, Aflahul (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2024)
Inventory management is an important part of business operations, especially in the sale of physical products, such as helmets. Aziz Helmet Store is a shop that focuses on the retail business of various types of helmets, considering that this product has various types of models, brands, sizes and with relatively dynamic market demand, effective stock management can help store inventory operations. With a waterfall model system development approach that focuses on implementing stock management applications using the FIFO method, it is hoped that it will be able to optimize inventory, ensure timely product availability, and overall increase customer satisfaction by providing the desired products when needed. The results of system testing using the black box approach show that the stock management application implementation design using the FIFO method was successfully implemented, this can be seen from the results of system function testing. Overall the user usability test value was 77.08%, this shows that the implementation of the stock management application is in accordance with needs. However, users still need to be given training regarding system operations and approaches to convince users about system security, user authorization and system authentication